(untitled) (Research, Society and Development, 2024)
Objective: This experience report aims to address the elaboration of the critical-reflective portfolio by medical students, based on practices in a basic health unit. Methodology: This is a qualitative experience report on the elaboration of the academic portfolio used by students of the seventh semester of the Faculty of Medicine of the Federal University of Pará (UFPA) on the experiences of the Teaching, Service and Community Integration Practice (PIESC) axis, which took place between March 18 and June 28, 2024. PIESC introduces students to the Basic Health Units (UBS) in order to expand the qualification of care.In this sense, the portfolio contributes to medical education, as each student performs a weekly pre-care of patients in the waiting room, then elaborates the diagnostic hypotheses and observes the medical conducts. At the end of the practice, he/she builds a critical-reflective text that will compose the academic portfolio. Result and Discussion: The stimulus to critical-reflective thinking is fundamental for the training of professionals committed to knowing and offering the best care, and this knowledge is acquired through the confrontation between knowledge and reality. Thus, the portfolio is an essential part of learning, as it motivates reflections based on clinical practice and fosters the preparation of more committed professionals. Conclusion: The creation of the portfolio encourages participation, discipline and concern with comprehensive patient care, aiming at the development of competencies and skills that allow a comprehensive view, beyond the disease.